Reaction kinetics of free and immobilized β-glucosidase in alginate gel - Jameel, Ahmad Tariq; Yusof, Faridah; Johana, Syaira (2013)
Kinetics and enzymatic activity of free and immobilized β-glucosidase by entrapment in calcium alginate beads was studied for the hydrolysis of p-nitrophenyl-β-D-glucopyranoside (PNPG). Three different sizes of beads, i.e., 3 mm, 4 mm and 5mm were studied and maximum activity was obtained in 4 mm beads, which was employed for subsequent studies. The enzyme activity was saturated beyond 0.04 mol/L of substrate for both immobilized and free enzyme. The entrapment resulted into decreased efficiency by 36.6% compared to free soluble enzyme. The hydrolysis rate data exhibit Michaelis-Menten kinetics. Michaelis constants obtained from linearized Langmuir plot are: vmax and Km as 21.10 μmol/mL.min and 0.0148 mol/L respectively for immobilized enzyme; vmax and Km for free enzyme were obtained as 24.33 μmol/mL.min and 0.0073 mol/L respectively. However, the immobilized β-Glucosidase did not show a satisfactory operational stability on reuse. Residual activity on the second and third use was found as 29 and 15 percent, respectively. The rates of enzyme reactions were also predicted theoretically using effectiveness factor relations for spherical particles and compared with the reaction rate for the free enzyme based on experimental data.